X-ray, UV, and optical time delays in the bright Seyfert galaxy Ark 120 with co-ordinated Swift and ground-based observations. Issue 1 (4th March 2020) - Lobban, A P; Zola, S; Pajdosz-Śmierciak, U; Braito, V; Nardini, E; Bhatta, G; Markowitz, A; Bachev, R; Carosati, D; Caton, D B; Damljanovic, G; Dębski, B; et al.
ABSTRACT: We report on the results of a multiwavelength monitoring campaign of the bright, nearby Seyfert galaxy Ark 120, using a ∼50-d observing programme with Swift and a ∼4-month co-ordinated ground-based observing campaign, pre-dominantly using the Skynet Robotic Telescope Network . We find Ark 120 to be variable at all optical, UV, and X-ray wavelengths, with the variability observed to be well correlated between wavelength bands on short time-scales. We perform cross-correlation analysis across all available wavelength bands, detecting time delays between emission in the X-ray band and the Swift V, B, and UVW1 bands. In each case, we find that the longer wavelength emission is delayed with respect to the shorter wavelength emission. Within our measurement uncertainties, the time delays are consistent with the τ ∼ λ 4/3 relation, as predicted by a disc reprocessing scenario. The measured lag centroids are τcent  = 11.90 ± 7.33, 10.80 ± 4.08, and 10.60 ± 2.87 d between the X-ray and V, B, and UVW1 bands, respectively. These time delays are longer than those expected from standard accretion theory and, as such, Ark 120 may be another example of an active galaxy whose accretion disc appears to exist on a larger scale than predicted by the standard thin-disc model. Additionally, we detect further inter-band time delays: most notably between the ground-based I and B bands (τcent  = 3.46 ± 0.86 d), and between both the Swift XRT and UVW1 bands and the I band (τcent  = 12.34 ± 4.83 and 2.69 ± 2.05 d, respectively), highlighting the importance of co-ordinated ground-based optical observations.